(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the incidence of acute toxicities, complications after one month follow-up, and treatment outcomes of concurrent chemoradiotherapy for nasopharyngeal carcinoma using intensity-modulated radiation therapy (IMRT) at Thai Nguyen Central General Hospital. Materials and Methods: A longitudinal descriptive study was conducted on 53 patients diagnosed with nasopharyngeal carcinoma who received concurrent chemoradiotherapy at Thai Nguyen Central General Hospital between June 2022 and June 2025. Results: Patients aged 50–59 years accounted for the highest proportion (30.8%), with a mean age of 53.6 ± 11.6 years. Stage III disease was the most common (66.0%). The most frequent acute hematologic toxicity was leukopenia, with grade 1, 2, and 3 incidences of 41.5%; 28.3%; 5.7%, respectively. The predominant renal toxicity was grade 1 creatinine elevation (35.8%). Oral mucositis occurred in 71.7% of patients, mostly grade 1. At one month after completion of concurrent chemoradiotherapy, hearing loss was the most common late complication, observed in 77.4% of patients, with grade 1 accounting for the majority (56.6%). Trismus was reported in 5.7% of patients. A complete response was achieved in 71.7% of cases, while 28.3% achieved a partial response. No disease progression was recorded.